Hermeneutics Perspective: Number and Personal Grammatical Equivalence of Google Translate - Berlin Insan Pratiwi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Due to translation process by Google Translate (GT) is recently common, analyzing its translation equivalence is required. Conducted as descriptive qualitative research, this content analysis study provides descriptions of number and personal equivalence aspects toward sentence meaning in hermeneutics view. There were 90 English sentences analyzed as research sample resulting 7 types of meaning equivalence phenomenon: 1) target text (TT) has number equivalent meaning and the sentence is hermeneutically accepted, 2) TT has no number equivalent meaning yet the sentence is hermeneutically accepted, 3) TT has no number equivalent meaning and the sentence is not hermeneutically accepted, 4) TT has personal equivalent meaning and the sentence is hermeneutically accepted, 5) TT  has no personal equivalent meaning yet the sentence is hermeneutically accepted, 6) TT has no personal equivalent meaning and the sentence is not hermeneutically accepted, and 7) both personal meaning equivalence and sentence hermeneutics point of view cannot be identified due to clusivity of Indonesian. It is concluded that GT is able to provide 53% meaning accuracy in terms of number aspect and 86.6% of number aspect sentences are hermeneutically accepted. GT provides 53% meaning accuracy in personal aspect and 73.3% of personal aspect sentences are hermeneutically accepted. Figures show higher hermeneutical acceptance than the meaning equivalent indicate that GT in Indonesian is considered to be understandable for basic need of clause and sentence level for common information in terms of number and personal equivalence, but for detailed information especially those of number, masculine/feminine, and clusivity phenomenon in Indonesian more enhancement for accuracy is needed.Keywords: meaning equivalence, hermeneutics, clusivity